Penyelesaian Tindak Pidana Penganiayaan yang Dilakukan oleh Anak Melalui Diversi - Syarah Annisa; Elly Sudarti (Fakultas Hukum, Universitas Jambi, 2021)
This article aims to find out the settlement of criminal acts of abuse committed by children through diversion at the Kerinci Police and the obstacles faced in the settlement of criminal acts of abuse committed by children through diversion at the Kerinci Police. This research uses empirical juridical method. Research results In the first case Police Report: LP/B-159/VIII/2020/SPKT.1/RES KERINCI. In the settlement that was resolved by diversion, an agreement was reached and was successful and in accordance with the rules in Article 7 paragraphs 1 and 2 of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. In the results of the diversion agreement Number: 03/HDK/XII/2020/RESKRIM dated December 03, 2020 In the second case the Police report: Number: B/58/II/Res.1.8/2021 In the settlement that was resolved by diversion, no agreement was reached. Through the results of the diversion agreement Number: 01/HKD/II/Res.1.8/2021 dated October 18, 2021. Obstacles faced in resolving criminal acts of abuse committed by children through diversion at the Kerinci Police, namely in solving cases there are difficulties during the investigation and in uniting thoughts between the victim and the child in conflict with the law so that an agreement can be reached and the issue can be resolved and not resolved. Â ABSTRAK Artikel ini bertujuan untuk mengetahui penyelesaian tindak pidana penganiayaan yang dilakukan oleh anak melalui diversi di Polres Kerinci dan kendala yang dihadapi dalam penyelesaian tindak pidana penganiayaan yang dilakukan oleh anak melalui diversi di Polres Kerinci. Penelitian ini menggunakan metode yuridis empiris. Hasil penelitian Pada kasus pertama Laporan Polisi: LP/B-159/VIII/2020/SPKT.1/RES KERINCI. Di dalam penyelesaian yang diselesaikan secara diversi telah tercapai kesepakatan dan berhasil dan sesuai dengan aturan di dalam Pasal 7 ayat 1 dan 2 Undang-Undang Nomor 11 Tahun 2012 Tentang Sistem Peradilan Pidana Anak. Pada hasil kesepakatan diversi Nomor: 03/HDK/XII/2020/RESKRIM tanggal 03 Desember 2020 Pada kasus kedua laporan Polisi: Nomor: B/58/II/Res.1.8/2021 Di dalam penyelesaian yang diselesaikan secara diversi tidak tercapai kesepakatan. Melalui hasil kesepakatan diversi Nomor: 01/HKD/II/Res.1.8/2021 tanggal 18 Oktober 2021. Kendala yang dihadapi penyelesaian tindak pidana penganiayaan yang dilakukan oleh anak melalui diversi di Polres Kerinci yakni pada penyelesaian kasus terdapat kesulitan pada saat penyelidikan dan dalam mempertemukan mereka yang berkonflik dengan hukum agar tercapainya kesepakatan persoalan tersebut dapat diselesaikan dan tidak terselesaikan.